The chosen factors determinative competitive bank - Černohorský, Jan (Univerzita Pardubice, 2004)
The competitiveness is actual topic at this time because all economy sectors including banking notify necessary changes. They discuss their readiness relative to competitiveness with expand to European Union. The aim of this paper is to introduce hypothesis which differentiate competitive and non-competitive banks.
Keywords: banky; finanční ukazatele; Konkurenceschopnost; hodnocení